Analysis of Stress Concentration in Orthotropic Laminates. (2016) - Kumar, Aditya; Agrawal, Akshay; Ghadai, Ranjan; Kalita, Kanak
Abstract: The current paper presents a comprehensive finite element analysis on stress concentration in orthotropic laminates. This research investigates the Stress Concentration Factor (SCF) in isotropic and orthotropic plates due to presence of a central cutout with respect to ply orientation angle (θ). The numerical simulations are carried out by using an 8 node shell element in ANSYS APDL environment. It is established from the simulations that the SCF is dependent upon the orientation the fibers. For orthotropic laminates, SCF depends on material properties. It increases with increase in Ey /Ex ratio and decreases with increase in μxy .